2013
DOI: 10.1111/1754-9485.12145
|View full text |Cite
|
Sign up to set email alerts
|

SPECT‐based functional lung imaging for the prediction of radiation pneumonitis: A clinical and dosimetric correlation

Abstract: SPECT-based DFH parameters appear to be useful as predictors of RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Marks et al [19] and Seppenwoolde et al [20] used SPECT-weighted parameters. Christian and co-workers [21] used mean perfusion-weighted lung dose, while Hoover et al [34] used normalised SPECT-weighted parameters. An alternative approach is segmentation of ''functional Abbreviations: NSCLC = non-small cell lung cancer; WHO = World Health Organisation; COPD = chronic obstructive pulmonary disease; GTV = gross tumour volume (t + n).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marks et al [19] and Seppenwoolde et al [20] used SPECT-weighted parameters. Christian and co-workers [21] used mean perfusion-weighted lung dose, while Hoover et al [34] used normalised SPECT-weighted parameters. An alternative approach is segmentation of ''functional Abbreviations: NSCLC = non-small cell lung cancer; WHO = World Health Organisation; COPD = chronic obstructive pulmonary disease; GTV = gross tumour volume (t + n).…”
Section: Discussionmentioning
confidence: 99%
“…Data on the ability of SPECT parameters to predict pulmonary toxicity are sparse. Recent study by Hoover et al [34] has investigated the role of SPECT parameters in the development of RP in a small patient cohort. The authors found SPECT-parameters (functional MLD, V20 and V30) to be better predictors of RP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex inflammatory molecular responses to ionising radiation in these tissues result in both bronchoalveolar fibrosis and vascular endothelial effects, which can cause pulmonary ventilation and perfusion deficits [2]. Imaging modalities capable of assessing ventilatory function and blood perfusion have demonstrated that these deficits can be observed and are associated with the clinical risk of toxicity [3][4][5][6]. Planar scintigraphy using 99m Tc-labelled macroaggregated albumin (MAA) is a longestablished imaging standard for functional ventilation/perfusion evaluation.…”
mentioning
confidence: 99%
“…As an example, FEV1/FVC, which represents the volume of air expired in the first second expressed as a percentage of FVC, was compared with the percentage of the WL volume with normal perfusion and ventilation. In addition, PFTs are routinely interpreted as a multiparametric examination, and isolated values such as FEV1 or DLCO, although directly impaired by local therapies, have only limited significance (33,34). Nevertheless, a cutoff value of 90% for %NVQ correctly classified 100% of patients without pulmonary function impairment and 91% of patients with significant pulmonary function impairment, whatever the underlying pathology (COPD or severe DLCO impairment).…”
Section: Discussionmentioning
confidence: 99%